(untitled) (Contemporary Mathematics, 2025)
This paper seeks to investigate and derive fixed point and common fixed point results for almost generalized contractive mappings and Reich contractions within the framework of partially ordered M-metric spaces. Furthermore, the practical utility and applicability of these findings are demonstrated through illustrative examples. The results presented herein build upon and substantially generalize several foundational studies in the existing literature.